Mergawe: A Picture of Changing Women's Tradition - Moh. Faiz Maulana (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2021)
This research focuses on women's efforts in placing themselves in the right position. In the midst of changing times that are so fast and open, women are faced with a feeling of dilemma. On the one hand, women are limited by traditions that always place them in the domestic sphere, which is commonly known as konco wingking. On the other hand, changing times or modernization has given women the freedom to enter the public sphere. Through moderation of the tradition, women in Paciran have managed to get out of their dilemma. They can maintain their traditions and identity as Javanese women and can create new traditions by accepting them as workers. Tradition moderation has also changed the meaning and view of the konco wingking tradition, which so far has only been considered a